Diversity and Equality Management System and Perceived Organisational Performance: A Mediating Role of Organisational Citizenship Behaviour. Issue 2 (May 2021) - Patnaik, Bignya; Shukla, Mahendra Kumar
A structured diversity and equality management system (DEMS) contributes to the smooth and peaceful functioning of organisations. The review of literature shows that the impact of DEMS on organisational performance and growth is found to be positive in Western countries. However, there appears to be a lack of research on the role of DEMS in Indian organisations, especially in the IT industry. This study makes an attempt to assess the impact of DEMS on perceived organisational performance and organisational citizenship behaviour (OCB) and empirically validate the mediating role of OCB in Indian IT firms. This study used descriptive research design, and the nature of research questions mandated the primary cross-sectional data collection method. The online questionnaire was e-mailed to human resource managers as well as executives of IT firms in India. Responses of 220 respondents were analysed to test the hypotheses of the research using CB-SEM. The results confirm a mediating role of OCB on the linkage between DEMS and perceived organisational performance. Findings suggest that organisations should promote OCB as it contributes significantly in establishing a positive, committed and conflict-free work environment.